JVM Internals and Its Impact on Application Performance - Sudhakar Reddy Narra, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the intricacies of Java Virtual Machine (JVM) internals and their critical impact on application performance in enterprise environments. The article examines core components including garbage collection mechanisms, memory management strategies, and threading models, providing detailed insights into how these elements affect overall system behavior. The article carefully examines various garbage collectors, memory allocation patterns, and thread contention scenarios, revealing key optimization strategies and their practical implications. The article encompasses real-world case studies, particularly focusing on e-commerce platforms, while also evaluating the effectiveness of diagnostic tools and monitoring solutions. By analyzing performance metrics across different operational scenarios, the article demonstrates how proper JVM tuning can significantly enhance application performance, reduce resource utilization, and improve system stability in production environments.
Keywords: JVM Optimization; Garbage Collection; Memory Management; Thread Contention; Performance Tuning